2012
DOI: 10.1097/cji.0b013e31826c8a4f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pemetrexed on Innate Immune Killer Cells and Adaptive Immune T Cells in Subjects With Adenocarcinoma of the Pancreas

Abstract: Baseline levels of innate and adaptive immune cell functions were studied in patients with pancreatic cancer. The effects of pemetrexed were measured at 7 and 14 days after initial therapy then 14 days after combination therapy with gemcitabine. Pretherapy levels of absolute numbers of natural killer (NK) cells positively correlated with survival. Cytolytic units of NK activity correlated positively with NK cell numbers. Pemetrexed decreased NK cytolytic units to significance when combined with gemcitabine. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…The direct correlation between NK cell number and cytotoxic function has been already noted by Davis et al 43 in pancreatic cancer patients and could derive from an alteration in NK cell proliferation and function, probably due to the profound tumor-dependent (at presurgery) and surgery-dependent (at 7 days postintervention) modulation of soluble factors. Indeed, the well-known deregulation of NK cell–modulating cytokines, such as IL-2, IL-12, and IL-18, and of CD4/CD25 regulatory T-cell subset in pancreatic cancer patients could set up an altered microenvironment, in which NK cells adopted aberrant proliferation, differentiation, and functional behavior.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The direct correlation between NK cell number and cytotoxic function has been already noted by Davis et al 43 in pancreatic cancer patients and could derive from an alteration in NK cell proliferation and function, probably due to the profound tumor-dependent (at presurgery) and surgery-dependent (at 7 days postintervention) modulation of soluble factors. Indeed, the well-known deregulation of NK cell–modulating cytokines, such as IL-2, IL-12, and IL-18, and of CD4/CD25 regulatory T-cell subset in pancreatic cancer patients could set up an altered microenvironment, in which NK cells adopted aberrant proliferation, differentiation, and functional behavior.…”
Section: Discussionsupporting
confidence: 56%
“…19 Natural killer cells may exert their protective role by killing pancreatic cancer cells, which have lost major histocompatibility complex class I expression 42 and/or express-induced ligands for NKG2D activating receptor, 38 and their increased cell number may represent an important defense against residual cancer cells; actually, a positive correlation between pancreatic cancer patient survival and their PB NK cell absolute count has been previously described. 43 …”
Section: Discussionmentioning
confidence: 99%
“…[73] The numbers of circulating NK cells are reduced in patients with advanced PC [29] , and pretreatment levels of peripheral NK cells positively correlate with survival in patients with PC. [32] These findings indicate that NK cells exert some control over tumor progression. Based on histologic evaluation, Ene-Obong et al [8] recently demonstrated reduction in numbers of NK cells and CD8 + T cells in the juxta-tumoral area as compared with the pan-stromal area of human PC, potentially due to sequestration and preferential migration to activated pancreatic satellite cells.…”
Section: Innate Immune Cells In Pcmentioning
confidence: 99%
“…In recent years, studies showed that pemetrexed could be used and had certain effects on a variety of commonly seen tumors like lung cancer, colorectal cancer, breast cancer and pancreatic cancer, etc.. (Gerber et al, 2013;Zhang et al, 2013;Deng et al, 2013;Davis et al, 2012). National Comprehensive Cancer Network (NCCN) guidelines (2009) recommended that after first-line treatment of platinum-containing regimen or monotherapy, NSCLC patients with SD were considered to be effective after 4~6 cycles of pemetrexed chemotherapy, who could continue the original chemotherapy or added with maintenance therapy until disease progression.…”
Section: Discussionmentioning
confidence: 99%